Carbon Nanotube Modified Microelectrode Array for Neural Interface - Vafaiee, Mohaddeseh; Mohammadpour, Raheleh; Vossoughi, Manouchehr; Asadian, Elham; Janahmadi, Mahyar; Sasanpour, Pezhman (Frontiers in Bioengineering and Biotechnology, 2021)
Carbon nanotubes (CNTs) coatings have been shown over the past few years as a promising material for neural interface applications. In particular, in the field of nerve implants, CNTs have fundamental advantages due to their unique mechanical and electrical properties. In this study, carbon nanotubes multi-electrode arrays (CNT-modified-Au MEAs) were fabricated based on gold multi-electrode arrays (Au-MEAs). The electrochemical impedance spectra of CNT-modified-Au MEA and Au-MEA were compared employing equivalent circuit models. In comparison with Au-MEA (17 Ω), CNT-modified-Au MEA (8 Ω) lowered the overall impedance of the electrode at 1 kHz by 50%. The results showed that CNT-modified-Au MEAs have good properties such as low impedance, high stability and durability, as well as scratch resistance, which makes them appropriate for long-term application in neural interfaces.